5(m-4)+6m=5(m+3)-7

Simple and best practice solution for 5(m-4)+6m=5(m+3)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(m-4)+6m=5(m+3)-7 equation:


Simplifying
5(m + -4) + 6m = 5(m + 3) + -7

Reorder the terms:
5(-4 + m) + 6m = 5(m + 3) + -7
(-4 * 5 + m * 5) + 6m = 5(m + 3) + -7
(-20 + 5m) + 6m = 5(m + 3) + -7

Combine like terms: 5m + 6m = 11m
-20 + 11m = 5(m + 3) + -7

Reorder the terms:
-20 + 11m = 5(3 + m) + -7
-20 + 11m = (3 * 5 + m * 5) + -7
-20 + 11m = (15 + 5m) + -7

Reorder the terms:
-20 + 11m = 15 + -7 + 5m

Combine like terms: 15 + -7 = 8
-20 + 11m = 8 + 5m

Solving
-20 + 11m = 8 + 5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5m' to each side of the equation.
-20 + 11m + -5m = 8 + 5m + -5m

Combine like terms: 11m + -5m = 6m
-20 + 6m = 8 + 5m + -5m

Combine like terms: 5m + -5m = 0
-20 + 6m = 8 + 0
-20 + 6m = 8

Add '20' to each side of the equation.
-20 + 20 + 6m = 8 + 20

Combine like terms: -20 + 20 = 0
0 + 6m = 8 + 20
6m = 8 + 20

Combine like terms: 8 + 20 = 28
6m = 28

Divide each side by '6'.
m = 4.666666667

Simplifying
m = 4.666666667

See similar equations:

| -10x^2+6x+3=0 | | 2(3x+4)+2x=11x-4+x | | Y=12x^2+24 | | 8x+1=6(1+3x)-2(5x-6) | | 3(2x-7+5x)=x-1 | | F(x)=12x^2+24 | | H=-16t^2+128t+5 | | -6a-36=-4(3a+3) | | 3x+129= | | -7y=-21+28 | | 1/2(x-5)=x-2 | | 4x+3/-5x-3=-1/2 | | 6v-5+5=6v | | (2x^2+6x-7)+(4x^2+2x+17)-(6x^2-11)= | | -4(4-7b)-3(4b-6)=-30 | | 6(x-2)-2x=-40 | | -147=-7(3-3r) | | A=3X(-1) | | 1+5m+7=-7 | | t*-1.5=8 | | -4*-1.5=6 | | -8(p-5)=109.6 | | 4-3x=4(3-x)-3x | | -0.1875*8=-1.5 | | (x^2+5x+5)-(5x^2-8x+7)= | | 8*t=-1.5 | | -4.45-2=-5.5s-4.2 | | -7k-5(-7k+7)=-3+4(7-8k) | | 6*t=-9 | | 6*(-9)=t | | -(h+7)=-8 | | 12-4n=-(n+1)-5 |

Equations solver categories